Drug Eruption and Hepatitis Induced by Antituberculosis Therapy: A Case Report: A Case Report - Rahman, Muhammad Ariq; Asfaroh, Lilis (Faculty of Medicine - Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Pulmonary tuberculosis remains a global health issue, with one of the challenges being the adverse side effects of anti-tuberculosis drugs that can interfere with the success of therapy. This case reports a 67-year-old man with pulmonary tuberculosis who experienced a rifampicin-induced drug eruption and pyrazinamide-induced hepatitis during first-line antituberculosis combination therapy. After temporarily discontinuing the antituberculosis regimen, the patient was given supportive therapy with corticosteroid and antihistamine for the drug eruption, and stronger neo-minophagen C injections for the hepatitis. After stabilization, the regimen was adjusted to a combination of isoniazid and ethambutol, and streptomycin was added as the third agent; however, due to an allergic reaction, streptomycin was replaced with levofloxacin. The new regimen, isoniazid-ethambutol-levofloxacin, combined with appropriate management of the adverse reactions resulted in favorable clinical outcomes, marked by the disappearance of the itchy red rash on the face and body, improvement in liver function as seen from liver enzymes and bilirubin levels, and a stable general condition. This case report emphasizes the importance of being aware of the adverse side effects of antituberculosis regimens, especially in elderly patients. Regular monitoring of liver function, early detection of drug reactions, and safe and individualized regimen adjustments are important strategies to prevent complications without compromising the success of tuberculosis treatment. This case provides important lessons regarding a cautious, evidence-based clinical approach to addressing serious side effects of antituberculosis drugs.